MICROORGANISMS’ SURFACE ACTIVE SUBSTANCES ROLE IN HYDROCARBONS BIODEGRADATION - Vasylchenko, Оlga; Matvyeyeva, Olena; Aliievа, Oksana (Proceedings of National Aviation University, 2012)
Existing data and publications regarding oil, hydrocarbon biodegradation, metabolism, and bioremediation were analyzed. Search of hydrocarbon degrading bacteria which are producers of biosurfactants was provided, types of microbial surfactants and their physiological role were analyzed and ordered. The study of factors affecting the surface active properties of producers’ cultures was done.